Chronological changes of 123I-MIBG myocardial scintigraphy and clinical features of Parkinson's disease. Issue 9 (2nd May 2015) - Tsujikawa, Koyo; Hasegawa, Yasuhiro; Yokoi, Satoshi; Yasui, Keizo; Nanbu, Ichiro; Yanagi, Tsutomu; Takahashi, Akira
Abstract : Objectives: The aim of this study was to investigate chronological changes of 123 I- meta -iodobenzylguanidine (MIBG) myocardial scintigraphy and its relation to clinical features in patients with Parkinson's disease (PD), and to characterise patients with PD with normal or mildly low MIBG uptakes at their early stages. Methods: The participants were 70 patients with PD who underwent 123 I-MIBG myocardial scintigraphy twice or more. A cluster analysis was performed using parameters calculated from heart to mediastinum (H/M) ratio and washout ratio (WR). Results: At baseline, the mean early H/M ratio (H/M(E)), delayed H/M ratio (H/M(D)) and WR were 1.83, 1.69 and 41.7%, respectively. After a mean interval of 3.0 years, follow-up studies showed significantly declined H/M(E) (1.69, p<0.001), declined H/M(D) (1.47, p<0.001) and enhanced WR (43.8%, p=0.007). Our longitudinal observations revealed that there existed heterogeneous changes in MIBG uptakes among patients. The cluster analysis classified the patients into two subgroups: 42 patients with markedly low MIBG uptakes at baseline (group A) and 28 patients with normal or mildly low MIBG uptakes at baseline (group B). Group B showed a significantly higher ratio of females, younger age at onset, lower Hoehn and Yahr stage and less demented, compared with group A. Conclusions: Follow-up studies of MIBG divided the patients with PD into two major subgroups. A subgroup of patients with PD with normal or mildly low MIBG uptakes at the early stages of illness was characterised by female-dominant, young onset, slow progression in motor dysfunctions and preserved cognitive function. Trial registration number: 1033.